(untitled) (Eurasian Journal of Ecology, 2016)
Results of a study of the anatomical structure of vegetative organs of rare and endemic species Limonium michelsonii in the early stages of ontogeny are presented in this article. Three populations of Limonium michelsonii in eastern part of Trans-Ili Alatau (mountain Bogutty and Toraigyr, Bartogay hole) were investigated for this. Age states of plants of Limonium michelsonii have been installed, the patterns of them were collected and fixated in each of the studied population for further study its anatomical structure. The internal structure of leaves and roots of individuals of Limonium michelsonii from different populations in the early stages of ontogeny has a great similarity was found and the specific differences in the anatomical structure of vegetative organs has not been established.